PENGARUH INFLASI, INVESTASI DAN TINGKAT SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT - B01108030, SYAHRIZAL NASUTION (Jurnal Pembangunan dan Pemerataan, 2015)
This thesisis titled â€œPengaruh Inflasi, Investasi dan Tingkat Suku Bunga Terhadap Pertumbuhan Ekonomi di Kalimantan Barat Tahun 2004-2013â€ In writing this thesis research is the method through quantitative methods associative clause approach using secondary data, in this case should also be pointed out that supporting data for analysis in this paper is a data-quarter of the period 2004.1 - 2013.4. The analysis technique used is multiple regression, while the statistical test using t-test to test the effect of variable and partially f trials to test the effect of variables simultaneously with a significant level of 5%. Based on the research results that inflation has a negative direction and significant effect on economic gowth, while investment and interest rates have a positive direction and significant effect on the economic growth in West Kalimantan. The results of the calculations, the F test showed that Fhit> F table is equal to 22,03071 > 2,87 which means that inflation, investment, and interest rates jointly significant effect on the economic growth in West Kalimantan. In the results of t-test results obtained expenditure inflation, investment, and interest rates have significant real and close to the economic growth. Key Words : Economic GrowthÂ  (dependent variable)Inflation (independent variable)Investment (Independent variable)Interest rates (independent variable)